2010
DOI: 10.1080/87565641003689556
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Callosal Microstructure in the Normal Adult Aging Brain Using Quantitative DTI Fiber Tracking

Abstract: We present a review of neuroimaging studies of normal adult aging conducted with Diffusion Tensor Imaging (DTI) and data from one of the first longitudinal studies using DTI to study normal aging. To date, virtually all DTI studies of normal adult aging have been cross-sectional and have identified several patterns of white matter microstructural sparing and compromise that differentiate regional effects, fiber type, and diffusivity characteristics: 1) fractional anisotropy (FA) is lower and mean diffusivity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
80
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(98 citation statements)
references
References 146 publications
(199 reference statements)
15
80
3
Order By: Relevance
“…Such uncertainty information may allow users to quantify the effects of DTI data quality on connectivity measurements, account for data quality in downstream analyses, and identify corrupted scans for which uncertainty is especially high [see Koltchinskii et al (2007) for more information] neuropathological processes presumably represent the most viable path toward understanding the relative time course of late-life white matter changes and how that time course is modulated by a complex array of inter-connected biological events. Yet, to our knowledge, there may be as few as three published studies related to cognitive aging that involve multiple DTI scans per human subject (Charlton et al 2010;Teipel et al 2010;Sullivan et al 2010). As noted above methodological issues related to DTI measurement reliability have made serial DTI studies difficult, but their importance for decoding the biology of cognitive aging is clear, and they will remain a future direction of study.…”
Section: Needs In Relation To Dti and Risk Factorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Such uncertainty information may allow users to quantify the effects of DTI data quality on connectivity measurements, account for data quality in downstream analyses, and identify corrupted scans for which uncertainty is especially high [see Koltchinskii et al (2007) for more information] neuropathological processes presumably represent the most viable path toward understanding the relative time course of late-life white matter changes and how that time course is modulated by a complex array of inter-connected biological events. Yet, to our knowledge, there may be as few as three published studies related to cognitive aging that involve multiple DTI scans per human subject (Charlton et al 2010;Teipel et al 2010;Sullivan et al 2010). As noted above methodological issues related to DTI measurement reliability have made serial DTI studies difficult, but their importance for decoding the biology of cognitive aging is clear, and they will remain a future direction of study.…”
Section: Needs In Relation To Dti and Risk Factorsmentioning
confidence: 95%
“…One study has suggested that by investigating relationships between FLAIR signal intensity and DTI measures within WMHs, we can effectively categorize WMHs according to the severity of WMH dysfunction, but the clinical value of such deeper characterization of WMH severity is currently unclear (Zhan et al 2009). Second, while several serial FLAIR studies have used multiple scans per individual to directly chart the longitudinal course of WMH changes in relation to risk factors and cognition, only three analogous serial DTI studies have appeared that report associations between DTI-based measures and ancillary variables of interest (Charlton et al 2010;Teipel et al 2010;Sullivan et al 2010). Third, while FLAIR is a longstanding MRI technology that is relatively easy to acquire, DTI is a recent development, with attendant problems related to data reliability and biases (see Sect.…”
Section: Relation To Flairmentioning
confidence: 97%
“…Indeed, even normal aging is characterized by an anterior-to-posterior gradient of microstructural degeneration along the CC (Sullivan et al, 2010) making regions of the isthmus/body of the CC, where CMF cross, particularly vulnerable to thinning. Fibers of the COF, which cross more posteriorly in the splenium of the CC, were not affected and thus delineated in all subjects.…”
Section: Limitationsmentioning
confidence: 99%
“…Boosted by the advent of more stable and high performance MR equipment, the interest to perform longitudinal DTI studies for capturing such subject-specific changes in microstructural organization is increasing rapidly (e.g., Concha et al, 2007;Deprez et al, 2012;Gong et al, 2008;Keller and Just, 2009;Kumar et al, 2009;Ljungqvist et al, 2011;Schlaug et al, 2009;Scholz et al, 2009;Sullivan et al, 2010;Yogarajah et al, 2010). Although there are several well-established methods for analyzing cross-sectional DTI data sets, they may not be 'optimal' for longitudinal studies.…”
Section: Introductionmentioning
confidence: 99%